Design of Accounting Learning Media for Vocational Students to Enhance Data Analytics Skills Using Microsoft Power BI - Fiddin, Fachroh; Rahmani, Nur; Amelda , Amelda; Dwikurnia, Via (ABEC Indonesia, 2024)
This research is motivated by the lack of learning media that facilitates the use of data analytics tools likeMicrosoft Power BI in vocational accounting education, despite the fact that several professional literatures highlight thataccountants need skills in working with data and communicating results to stakeholders. The purpose of this study is todesign a learning media based on accounting data in the form of several financial dashboards, including sales analysis,Profit & Loss analysis, and Balance Sheet analysis, using financial transaction data processed through Microsoft Power BI.This enables both lecturers and students to interpret accounting data through the data visualization tools that have beencreated.This study follows a developmental research approach using the ADDIE model, which includes analysis, design,development, implementation, and evaluation. The testing of this learning media design was conducted with accountinglecturers and students. The results show that the validation from both lecturers and students indicates that the learningmedia received excellent ratings. Therefore, it can be concluded that the learning media utilizing Microsoft Power BI toenhance students' data analytics skills is highly feasible for implementation in accounting education.